SYNTHESIS OF NANOCOMPOSITE (alpha)-Fe2O3/SiO2 BY SALT-ASSISTED SPRAY PYROLYSIS METHOD FOR REDUCING VISCOUSITY OF HEAVY OIL - SAMSUL ANROKHI (NIM: 20210009); Pembimbing: Dr.Eng. Ferry Iskandar dan Prof. Dr.Eng. Mikraju, MOHAMAD
Heavy oil, the largely available oil is still difficult to produce as it has a relativly high viscousity. So far, the process used to reduce its viscousity has not been efficient and not economical. Therefore, the more efficient and economical process to reduce its viscocity is extremely needed. The method is to add metal oxide nanocomposite catalysts (alpha)-Fe2O3/SiO2. (alpha)Fe2O3/SiO2 is synthesized by Salt-Assisted Spray Pyrplysis method. The (alpha)Fe2O3/SiO2 powder resulting be expected can reducing viscosity of heavy oil. The (alpha)Fe2O3/SiO2 nanocomposite is obtained by thermal decomposition of the droplet. The droplet generated from the precursor by nebulizer. The precursor is made of FeCl3 solution, SiO2 solution and NaCl solution. Concentration of FeCl3, SiO2, and NaCl are 1:1:5 in order. the composition of SiO2 in the composite is 0percent , 25percent and 50 percent of total mass, respectively. the precursor is sprayed to form droplets and then the droplets were transported to the furnace reactor using air as a carrier gas with a fixed flow rate at 5 liter/min and the furnaces temperature is 8000C in order to get the pyrolysis reaction. The resulted powder is then characterized. The result of XRD characterization shows that crystal peaks of (alpha)Fe2O3 has been formed. SEM result shows nanocomposite morphologi of (alpha)-Fe2O3/SiO2 with circle particle form. Diametre particle of (alpha)-Fe2O3 without the addition of SiO2, with the addition of SiO2 25 percent of total mass, and 50 percent of total mass are 765 nm, 850 nm, and 746 nm, respectively. The temperature versus the oil flow test showed catalyst (alpha)-Fe2O3/SiO2 50 percent could reduce viscosity of heavy oil better than (alpha)-Fe2O3 and (alpha)-Fe2O3/SiO2 25 percent.